Association of Central Obesity with Cardiovascular Diseases - Malik Faisal Iftekhar, Said Zaman, H.m. Saadan Saqib, Arshad Ali Shah, Syed Dilbahar Ali Shah, Misdaq Batool (Pakistan Journal of Medical & Health Sciences, 2022)
Background: An increased trend of central obesity in general population has increased their risk of cardiovascular disease in various populations. Aims: To find an association between central obesity and cardiovascular disease. Study Design: Survey based study Place and Duration of Study: Department of Cardiology, MTI Lady Reading Hospital, Peshawar from 1st October 2020 to 30th September 2021. Methodology: Four hundred and twenty community participants were assessed for their central obesity via waist circumference measurement. Their lipid profiling, fasting blood sugar and exercise tolerance test was also conducted. Results: The mean age was 56.77±12.6 years with 61.9% females and 38.09% as male participants. The waist circumference ≥90cm in males was 7.5% while it was 15.3% in females. The socioeconomic status of the males and females with higher waist circumference was more as low to middle class. The odds ratio comparison within males and females showed a significant variance among ages, BMI and socioeconomic status in term of family income. The biochemical analysis of various participants blood samples showed dyslipidemia, ischemia and risk of atherosclerosis to be higher in central obesity participants than normal weight (p value <0.005). Conclusion: There is a strong association of central obesity and cardiovascular diseases.